A comparative study of Fentanyl and Clonidine as additives to plain Bupivacaine in caudal anaesthesia in children - Malarvizhi, T.; Kannan, Kannan; Rajesh, Rajesh; Poornima, Poornima (International Journal of Medical Research and Review, 2017)
Introduction: The efficacy of clonidine or fentanyl as additives to alter the neuroendocrine stress response and emergence agitation in caudal anaesthesia in children is still not clear. Objectives: To compare the efficacy and safety of Fentanyl and Clonidine as additives to plain bupivacaine in caudal anaesthesia in children. Materials & Methods: A prospective, open labeled randomized controlled trial was conducted in Meenakshi Mission Hospital and Research Centre, Madurai, between August 2008 to June 2010. Children undergoing various elective infra-umbilical surgical procedures were included. Children were randomly assigned to either 0.5% Bupivacaine(B), Fentanyl plus 0.5% Bupivacaine (BF) or Clonidine Plus 0.5% Bupivacaine(BC) groups. Results: A total of 90 children, with 30 subjects in each of the three intervention groups were included. Time taken for spontaneous movement was significantly higher (151.8±11.7) in BC group, as compared the other two groups. The duration of postoperative analgesia was lowest in Bupivacaine (146±91.2) alone group, followed by BF (293.5±154.5) and BC group (510±359.9). Sedation time also has shown a similar trend. The mean pain scores from 2 hours to 24 hours were highest in bupivacaine group, followed by BF and BC group. The differences in the sedation scores across the three study groups from 45minutes to 24-hour post-operative period were statistically significant. Conclusions: Addition of clonidine 1µg/kg to 0.5% bupivacaine prolonged the duration of postoperative analgesia after a single shot caudal injection without any significant side effects when compared to bupivacaine 0.5% alone or its combination with fentanyl 1µg/kg.